Implementation of Assignment Method in Improving Teachers' Ability to Analyzing SK (Competency Standards) and KD (Basic Competencies) at SMPN 1 Tapung Hulu Kampar - Kresna, Pharada (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper describes how the assignment method can improve teachers' abilities in analyzing SK and KD at SMPN 1 Tapung Hulu Kampar. Based on the description of the background, problem identification, and problem limitation, the focus of the research is related to the implementation of assignment methods to improve teachers' abilities in analyzing SK and KD at SMPN 1 Tapung Hulu Kampar. The research action hypothesis is "if the assignment method is applied, it can improve teachers' abilities in analyzing SK and KD at SMPN 1 Tapung Hulu Kampar Regency”. The type of research is school action research (PTS), which stands for determining the success of implementing the assignment method to improve teachers' abilities in analyzing SK and KD at SMPN 1 Tapung Hulu Kampar. The research location is at SMPN 1 Tapung Hulu Kampar. This research was carried out in February 2023 and the number of samples in the research was 28 teachers. Based on the description of data processing and discussion, it is concluded that the teacher's ability to analyze SK and KD was found in cycle I at 64.5% in the quite good category and in cycle II it increased to 77.9% in the good category.